2014
DOI: 10.1107/s139900471400916x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of liganded T-state haemoglobin from cat (Felis silvestris catus), a low oxygen-affinity species, in two different crystal forms

Abstract: Haemoglobin (Hb) is an iron-containing metalloprotein which plays a major role in the transportation of oxygen from the lungs to tissues and of carbon dioxide back to the lungs. Hb is in equilibrium between low-affinity tense (T) and high-affinity relaxed (R) states associated with its unliganded and liganded forms, respectively. Mammalian species can be classified into two groups on the basis of whether they express `high' or `low' oxygen-affinity Hbs. Although Hbs from the former group have been studied exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Hydrogen bonds and salt bridges at the IsdH N2N3 -metHb interface are shown in Table 2. Symmetry-related dimers form a Hb tetramer in the crystal; however, the relative positioning of dimers does not correspond to the canonical T (low O 2 affinity) or R (high O 2 affinity) quaternary structures of Hb (Perutz et al, 1960;Muirhead & Perutz, 1963) and is more similar to two recently determined structures of fully liganded Hbs with a T-like quaternary structure (Safo et al, 2013;Balasubramanian et al, 2014; discussed further below).…”
Section: Overall Structure Of the Isdh N2n3 -Methb Complexmentioning
confidence: 62%
See 2 more Smart Citations
“…Hydrogen bonds and salt bridges at the IsdH N2N3 -metHb interface are shown in Table 2. Symmetry-related dimers form a Hb tetramer in the crystal; however, the relative positioning of dimers does not correspond to the canonical T (low O 2 affinity) or R (high O 2 affinity) quaternary structures of Hb (Perutz et al, 1960;Muirhead & Perutz, 1963) and is more similar to two recently determined structures of fully liganded Hbs with a T-like quaternary structure (Safo et al, 2013;Balasubramanian et al, 2014; discussed further below).…”
Section: Overall Structure Of the Isdh N2n3 -Methb Complexmentioning
confidence: 62%
“…The iron-iron distance between haems of IsdH N2N3 -metHb (Table 4; 38.3 Å ) also indicated closer similarity to the T state (39.5 Å ) than to the R state (34.9 Å ). Using the same criteria (Tables 3 and 4), two other Hb structures in the PDB show much greater levels of similarity to IsdH N2N3 -metHb, namely a human Hb variant comprising embryonic chain and chain carrying the sicklecell mutation ( S ) crystallized in the fully CO-ligated form (Safo et al, 2013) and metHb from cat (Felis silvestris catus; Balasubramanian et al, 2014). Both the Hb 2 2 S and cat metHb structures exhibit an unusual T state-like quaternary structure with several local tertiary and quaternary features characteristic of the R state (Safo et al, 2013;Balasubramanian et al, 2014).…”
Section: Altered Hb Quaternary Structurementioning
confidence: 99%
See 1 more Smart Citation
“…This interpretation agrees with the minor role of the β-subunit Nterminus in DPG binding (Richard et al, 1993) compared with the original model for DPG binding proposed by Arnone (1972). In addition to impairing DPG binding, the β2His→Phe substitution that exchanges a basic residue with an apolar one also contributes to the reduced intrinsic O 2 affinity typical of feline Hb isoforms by moving the β-chain N-termini towards the center of the Hb molecule, thereby stabilizing the T-state conformation (Perutz et al, 1993;Safo and Abraham, 2001) even when the heme is fully ligated, as found for domestic cat Hb (Balasubramanian et al, 2014). Similarly, the low O 2 affinity and DPG insensitivity of bovine Hb is also attributable to amino acid substitutions in the β-subunit N-termini (β1Val deleted and β2His→Met), which stabilize the low-affinity T state and prevent DPG access to the central cavity (Perutz et al, 1993;Safo and Abraham, 2001).…”
Section: Oxygenation Properties Of Big Cat Hbsmentioning
confidence: 92%
“…The column was preequilibrated with water and the hemolyzed sample was gently loaded on the column. Initially the column was washed with water to elute the unbound proteins, thereafter eluted with a gradient of NaCl salt solution, ranging from 0.1 M to 1 M, by stepwise increasing of 0.1 M. The bound hemoglobin was eluted at 0.1 M NaCl gradient elution and collected at a rate of 3 ml/min [10,[21][22][23][24][25][26][27][28]. The homogeneity of hemoglobin samples was analyzed by using SDS-PAGE [29].…”
Section: Puri Cation and Crystallizationmentioning
confidence: 99%